2020
DOI: 10.1155/2020/4736152
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Chemical Profile on “Activity Fingerprint” of Citri Reticulatae Pericarpium from Different Cultivars Based on HPLC‐UV, LC/MS‐IT‐TOF, and Principal Component Analysis

Abstract: Citri Reticulatae Pericarpium (CRP), known as Chenpi (CP) in Chinese, is a medicinal food for health and fitness. In order to find out the characteristic activity chemicals distinguishing various cultivars of CRP and provide a reference for effective development of citrus resources, an “activity fingerprint” of CRP from 21 different cultivars was established based on the evaluation of antitussive and expectorant activities. There were 18 common peaks in the HPLC fingerprint, of which 3 flavonoid glycosides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The powder in the solution was extracted by ultrasonic treatment in a KQ-800KDE instrument (Kunshan Ultrasonic Instruments Co. Ltd, China) for 30 min at 320 W (40 kHz) and then filtered to obtain sample solution A, which was subjected to HPLC-PDA analysis and total flavonoid content (TFC) and total phenolic content (TPC) determination. 18 Similarly, 0.2 g of dried sample powder (0.8 g of fresh peel pieces) with 20 mL of ethyl acetate was extracted twice and the filtrates were combined to obtain sample solution B, which was used for determination of total polymethoxyflavone content (TPMFC).…”
Section: Sample Preparation For Uv-visible and Hplc-pda Analysesmentioning
confidence: 99%
“…The powder in the solution was extracted by ultrasonic treatment in a KQ-800KDE instrument (Kunshan Ultrasonic Instruments Co. Ltd, China) for 30 min at 320 W (40 kHz) and then filtered to obtain sample solution A, which was subjected to HPLC-PDA analysis and total flavonoid content (TFC) and total phenolic content (TPC) determination. 18 Similarly, 0.2 g of dried sample powder (0.8 g of fresh peel pieces) with 20 mL of ethyl acetate was extracted twice and the filtrates were combined to obtain sample solution B, which was used for determination of total polymethoxyflavone content (TPMFC).…”
Section: Sample Preparation For Uv-visible and Hplc-pda Analysesmentioning
confidence: 99%
“…The differences between our results and those of previous studies might be due to the differences in the cultivars and aging periods of the samples. Zheng et al [22] compared the similarity and difference among various cultivars through principal component analysis (PCA). The results showed that compared with Citrus reticulata cv.…”
Section: Measurement Of Total Phenolics and Flavonoids Contents In Pc...mentioning
confidence: 99%
“…Our results are different from the findings of Luo et al [23] who reported that the contents of 5-dimethylnobiletin and naringin in PCR-C increased first and then decreased. The reasons of the differences could be related to the different origins [25], cultivars [22,26], PCR-C harvest period [27], and storage conditions [28]. However, using PCA and orthogonal partial least squares discriminant analysis, Luo et al [23] found that samples aged for 3, 5, and 10 years were clearly separated, indicating that the metabolites changed significantly during aging.…”
Section: Tracing the Variation Of Free And Bound Flavonoids In Pcr-c ...mentioning
confidence: 99%
“…However, chloroform and hexane are not compatible with ESI so it was necessary to blow dry these substances with nitrogen and dissolve them with methanol before the analysis. Methanol was also used as extraction of PMFs in recent studies [5,18,25]. Moreover, methanol is conducive to ESI, which saved time in drying extracting solutions.…”
Section: Optimization Of Sample Extraction and Instrument Settingsmentioning
confidence: 99%
“…Moreover, fingerprint methodology and the metabolomics approach were also applied to identify GCP [9,10]. Additionally, recent studies reported that the chemical components of GCP mainly included volatiles, flavonoids, alkaloids, and phenolic acids [11][12][13][14]; most studies concentrated on volatiles [15,16] and flavonoids [17][18][19][20]. Rich in volatiles, C. reticulata Blanco and C. reticulata 'Chachi' were analyzed by gas chromatography coupled with mass spectrometry (GC-MS) in several laboratories over the past decades [21,22].…”
Section: Introductionmentioning
confidence: 99%